It Is Not That Simple nor Compelling!: Comment on "Translating Evidence Into Healthcare Policy and Practice: Single Versus Multi-faceted Implementation Strategies – Is There a Simple Answer to a Complex Question?" - Bucknall, Tracey (Int J Health Policy Manag, 2015)
Healthcare decisions are often made under pressure, with varying levels of information in a changing clinical context. With limited resources and a focus on improving patient outcomes, healthcare managers and health professionals strive to implement both clinical and cost-effective care. However, the gap between research evidence and health policy/clinical practice persists despite our best efforts. In an attempt to close the gap through behaviour change interventions, there has been a strong held belief that ‘more is better,’ without understanding the mechanisms and circumstances of knowledge translation (KT). We argue that even a single intervention or strategy in translating evidence into healthcare policy or practice is rarely simple to implement. Nor is the evidence compelling on the best approach. As Harvey and Kitson argued, designing and evaluating KT interventions requires flexibility and responsiveness. If we are to move forward in translation science then we need to use rigorous designs such as randomised controlled trials to test effectiveness of interventions or strategies with embedded process evaluations to understand the reason interventions do or do not work!